2009
DOI: 10.1142/s0219720009004060
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of Minisatellite Maps Based on Run-Length Encoding Scheme

Abstract: Subsequent duplication events are responsible for the evolution of the minisatellite maps. Alignment of two minisatellite maps should therefore take these duplication events into account, in addition to the well-known edit operations. All algorithms for computing an optimal alignment of two maps, including the one presented here, first deduce the costs of optimal duplication scenarios for all substrings of the given maps. Then, they incorporate the pre-computed costs in the alignment recurrence. However, all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…The latter provides a non-ambiguous version of the algorithm by Abouelhoda et al (2009), and is technically interesting because it combines a two-track problem (minisatellite aligment) with a non-trivial single-track sub-problem (reconstruction of duplication histories).…”
Section: Discussionmentioning
confidence: 99%
“…The latter provides a non-ambiguous version of the algorithm by Abouelhoda et al (2009), and is technically interesting because it combines a two-track problem (minisatellite aligment) with a non-trivial single-track sub-problem (reconstruction of duplication histories).…”
Section: Discussionmentioning
confidence: 99%
“…Given a cost for each operation, an optimal alignment is the one of minimum cost. An efficient algorithm for finding optimal map alignments is ARLEM [18]. …”
Section: Methodsmentioning
confidence: 99%
“…It is based on a compression technique to save redundant computations and its speed is not affected by any increase in the number of types. In [18], we reported that ARLEM is 18 to 24 times faster than the previously available algorithm MS_ALIGN, using real and artificial datasets. For further speed-up, the options for computing phylogeny, analyzing structure variations, and duplication dynamics run in parallel over a computer cluster of four nodes, where each node contains two Quadcore CPUs (2.5 GHz each) with 64 GB RAM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Run-length encoding was also used by Bérard et al [8], who proposed an O(n3+|Σ|ñ3) time and O(n2+|Σ|ñ2) space algorithm. Abouelhoda et al [9] gave an algorithm with an alphabet size independent time and space complexities of O(n2+nñ2) and O ( n 2 ), respectively. A detailed comparison between the different problem models appears in Section “A comparison with previous works”.…”
Section: Introductionmentioning
confidence: 99%